Approaches of climate factors affecting the spatial variation of annual gross primary productivity among terrestrial ecosystems in China. (March 2016) - Zhu, Xian-Jin; Yu, Gui-Rui; Wang, Qiu-Feng; Gao, Yan-Ni; He, Hong-Lin; Zheng, Han; Chen, Zhi; Shi, Pei-Li; Zhao, Liang; Li, Ying-Nian; Wang, Yan-Fen; Zhang, Yi-Ping; et al.
Graphical abstract: Highlights: Annual mean temperature (MAT) and CO2 ( ρ cyr ) enhanced radiation use efficiency (RUE). Annual precipitation (MAP) prompted fraction of absorbed annual PAR (FPARyr ). MAT and ρ cyr affected the spatial variation of annual GPP through altering RUE. MAP affected the spatial variation of annual GPP through altering FPARyr . Abstract: Analyzing the approaches that climatic factors affect the spatial variation of annual gross primary productivity (GPPyr ) would improve our understanding on its spatial pattern. Based on network eddy covariance measurements and published data in literature, we separated GPPyr into radiation use efficiency (RUE) and annual absorbed photosynthesis active radiation (APARyr ), where APARyr can be regarded as the product of the fraction of absorbed annual photosynthesis active radiation (FPARyr ) and annual PAR (PARyr ). Given that PARyr affects the spatial variation of GPPyr directly through itself, we investigated factors affecting the spatial variations of RUE and FPARyr, to reveal how climatic factors affect the spatial variation of GPPyr . Results suggest that the spatial variation of RUE was directly affected by annual mean air temperature (MAT) and annual mean CO2 mass concentration ( ρ cyr ). The increasing MAT and ρ cyr directly enhanced RUE. The increasing annual precipitation (MAP) directly prompted FPARyr . Therefore, MAT and ρ cyr affected the spatial variation of GPPyr through altering RUE while the effect of MAP was achieved through altering FPARyr . Our study could also provide an alternative way for regional GPPyr assessment.